Does presenting perpetrator and innocent suspect faces from different facial angles influence the susceptibility of eyewitness memory? An investigation into the misinformation effect and eyewitness misidentification - Deering, Kara; Colloff, Melissa F.; Bennett, Tia C.; Flowe, Heather D. (Frontiers in Psychology, 2024)
This study employed a misinformation paradigm to explore the effects of face angle on lineup discrimination accuracy, or the ability to distinguish guilty from innocent suspects. In our between-subjects experimental design, participants were presented with a staged crime, with the perpetrator's face viewed from the front or profile angle. Following this, participants read a crime report featuring an innocent suspect's image, shown from the same or different angle as the perpetrator. A subsequent lineup was conducted, wherein we manipulated both the presence of the perpetrator and the viewing angles of the faces (front or profile). The findings revealed no significant difference in identification errors as a function of viewing angle congruency across the stages of the misinformation paradigm. However, participants demonstrated higher discrimination accuracy when faces were shown from the front angle, both during the initial event and the lineup, compared to the profile angle. This underscores the importance of considering viewing angles in the construction of lineups in legal contexts.